Alexandre e outros heróis, do texto à tela - SANTOS, Wanderson de Freitas dos (2023)
The book Alexander and other heroes, written by Graciliano Ramos, published in 1944 as The Tales of Alexander and republished posthumously in 1962 with the current title, presents Alexander, an old man with a crooked eye, who tells stories in an exaggerated and imaginative way. In 2013, this work was adapted into a film of the same name, directed by Luiz Fernando Carvalho and released in the same year on Globo TV. Hence, this work develops a comparative study between the work of Graciliano Ramos and the cinematographic adaptation of Carvalho, in order to interpret the possible meanings of the similarities and differences between the two works. The first chapter addresses the relationship between literature and cinema, and the adaptation process as an intensifying element of this approximation. The second chapter offers a study on the narrative focus in literature and cinema. The third chapter, on the other hand, presents an analysis of the literary text Alexandre and other heroes and the homonymous film adaptation. This analytical and bibliographic research, includes the analysis of the two productions and the support of some theorists and scholars, such as: Genette (2017), Stam (2006), Gaudreault (2009) and Hutcheon (2013). Using the perspective of Vanoye and Goliot Lété (1994), it is understood that Luiz Fernando Carvalho, even presenting your vision in the film, adapts the text from Graciliano and captures the characteristics of each narrative layer of the book, remaining structurally similar to the work of the writer from Alagoas.